Al-‘Alāqah baina Ushūl al-Fiqh wa Maqāshidi al-Sharīah wa al-Da’wah ilā Ta’sīsi ‘Ilmi al-Maqāshid (UINSI Samarinda, 2016)
The study of Maqāshid sharīa is an important point in the discussion of Islamic legal theory (ushūl al-fiqh). Serious debates began to emerge in the 19th century among Islamic jurists concerning the position of maqāshid sharīa. At least, there are three important debates in the history; first, whether maqāshid is part of the discussion ushūl al-fiqh; second, is maqāshid sharīa built upon a foundation of classical Islamic jurisprudence (fiqh); and third, whether the maqāshid sharīa study is able to become an independent science that is separated from the study of classical Islamic jurisprudence. This article tries to present a discussion of the three paradigms by employing a descriptive-analytic method. The results of this study uncover that the study of maqāshid sharīa is like two sides of one coin; theoretically it is a distinctive study from ushūl al-fiqh, but it cannot be separated from one another. Ushūl al-fiqh has become the foundation to find out more details about the study of maqashid sharia. The separation between classical Islamic jurisprudence (fiqh) and maqāshid sharīa study conducted by Islamic jurists is a relative separation. Keywords: Ushūl al-fiqh, maqāshid sharīa, separation between Ushūl al-fiqh and study of maqāshid sharīa.